An Education Only at the Service of Capital or of the Human Being Understood Integrally? Critical Analysis of the OECD Report on Education in Costa Rica - Chaverri-Chaves, Pablo (2026)
Introduction. This article presents a critical analysis of the report: OECD Economic Surveys: Costa Rica 2023 (OECD, 2023b). Purpose. Critically review this report, understanding the vision of education that is proposed and its implications. Discussion. The report is analyzed, in terms of its vision of education, the educational system, and national development. Initially, the report is put into context, after which the observations of this document on the Costa Rican education system are presented and discussed, making a critical assessment of them. Conclusions. The OECD report for Costa Rica focuses on the relationship between education, employment, and the economy, losing sight of other key variables in the development of people and societies.